Strengthening Islamic Religious Education In Forming Legal Awareness Of Indragiri Hilir Correctional Citizens - Komariah, Nur; Wahyuni, Fitri; Suriyah, Suriyah; Ibrahim, Rusli; Hartati, Herni (CV. Pustaka An Nur, 2025)
Violations of the law committed by various groups, including political elites and law enforcers, indicate low legal awareness and practice of religious values ​​in society. This community service aims to build legal awareness and religious understanding for female Correctional Inmates (WBP) at the Class IIA Tembilahan Correctional Institution, Indragiri Hilir, Riau. The method used is Participatory Action Research (PAR) with an approach of observation, interviews, lectures, and worship practices. Activities are carried out every Friday for one year (January–December 2024), covering religious material (Al-Quran, tauhid, fiqh, morals) and law (criminal sanctions, legal awareness). The results of the community service show an increase in WBP's understanding of religion in worship practices such as prayer and thaharah, as well as a growing awareness of the legal consequences of the crimes they commit. However, the ability to read the Qur'an has not fully reached the target. This activity also has a positive psychological impact, such as regret for mistakes and determination not to repeat violations. The implication is that holistic assistance based on religion and law can be an effective model in fostering prisoners for better social reintegration.